1988
DOI: 10.1111/j.1469-7998.1988.tb03763.x
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering strategies of the badger, Meles meles, at 57 °N

Abstract: With 7 figures in the text)Over two eight-month periods (October/November-May) during successive winters (1983/4 and 1984/5), the body temperatures and activity patterns of captive badgers, Meles rneles, living under semi-natural conditions, were studied at 57 "N in Scotland. Temperature-sensitive radio transmitters and automated telemetry systems provided long-term records of body temperatures and times badgers were absent from an artificial sett.Badger body temperatures of 28-34 "C, significantly below euth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…Badger setts, however, are usually situated in the core area of the territories (Doncaster and Woodroffe 1993) and are hence only rarely visited by intruders (Kruuk 1989). In winter, badgers are less active and often stay underground for the majority of the night (Fowler and Racey 1988). During the mating season, males patrol the sett, investigating the different sett entrances to find oestrous females ( Stewart 1997, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Badger setts, however, are usually situated in the core area of the territories (Doncaster and Woodroffe 1993) and are hence only rarely visited by intruders (Kruuk 1989). In winter, badgers are less active and often stay underground for the majority of the night (Fowler and Racey 1988). During the mating season, males patrol the sett, investigating the different sett entrances to find oestrous females ( Stewart 1997, pers.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these areas, tapirs were more nocturnal in hotter days and more diurnal in the colder days. The decrease of diurnal activity and increase of nocturnal activity during higher temperatures was also related to large and medium mammals as lynxes (Beltrán and Delibes 1994), jackals (Ferguson et al 1988), bears (Garshelis and Pelton 1980), martens (Zielinski et al 1983) and badgers (Fowler and Racey 1988). In intermediate temperatures, tapirs used both covered and open areas, but the open areas were used in these temperatures only.…”
Section: Article In Pressmentioning
confidence: 96%
“…The results of our studies showed that the daily activity of the European badger in popula- Weather conditions are considered among the factors determining the daily activity of the badger (Neal, 1948;Cresswell & Harris, 1988;Fowler & Racey, 1988), as well as human and predator impact (Goszczyński et al, 2005;Rosalino et al, 2005). However, the population density of the wolf (Canis lupus (Linnaeus, 1758)) and lynx (Lynx lynx (Linnaeus, 1758)) (the main predators of the badger) is not high in most of Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers note a negative correlation between the duration of badger activity and the duration of daylight and the intensity of moonlight (Neal, 1948, Cresswell & Harris, 1988, Fowler & Racey, 1988. However, in some populations the European badger begins to leave the shelters before dark as the length of the daylight increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation